Current strategies to prevent ishcemia reperfusion injury in organ transplantation - Stringa, Pablo Luis (2014)
Solid organ transplantation is inherently associated to ischemia reperfusion injury (IRI) since the operative procedure always impliesthe harvesting, preservation and implantation of the organ,whichresult in several hours of ischemia followed by reperfusion. Several strategies have been proposed to mitigate IRI in organ transplantation.However, most of them are in experimental phases and currently few are implemented in the clinical field. These strategies can be applied in 3 different stages of the transplantation procedure: on the organ donor, known as donor pre-treatment; during preservation, when ischemic organ is waiting to be implanted in the recipient or on the transplant recipient. In the present review, we will discuss the different approaches to control IRI damage in solid organ transplantation and the rationale behind them.